Genetic factors underlying tacrolimus intolerance after liver transplantation - Liu, Yuan; Wang, Rui; Wen, Peizhen; An, Wenbin; Zheng, Jinxin; Zhang, Tao; Zhang, Pengshan; Wang, Haoyu; Zou, Fan; Pan, Hui; Fan, Junwei; Peng, Zhihai (Frontiers in Immunology, 2022)
Background Tacrolimus (FK506) is the cornerstone of immunosuppression after liver transplantation (LT), however, switching from FK506 to cyclosporine (SFTC) in clinical practice is common for LT patients intolerant of tacrolimus. We aimed to explore the genetic risks for patients with tacrolimus intolerance in this study. Methods A total of 114 LT patients were enrolled in this retrospective study. SNPs were genotyped using Infinium Human Exome-12 v1.2 BeadChip, and genome-wide gene expression levels were profiled using Agilent G4112F array. Results SFTC is a potential risk factor of dyslipidemia (OR=4.774[1.122-20.311], p = 0.034) and insulin resistance (IR) (OR=6.25[1.451-26.916], p = 0.014), though not influencing survival of LT patients. Differential expression analysis showed donor CYP3A5, CYP2C9, CFTR, and GSTP1, four important pharmacogenetic genes were significantly up-regulated in the tacrolimus intolerance group. Twelve SNPs of these four genes were screened to investigate the effects on tacrolimus intolerance. Regression analysis showed donor rs4646450 (OR=3.23 [1.22-8.60] per each A allele, p = 0.01), donor rs6977165 (OR=6.44 [1.09-37.87] per each C allele, p = 0.02), and donor rs776746 (OR=3.31 [1.25-8.81] per each A allele, p = 0.01) were identified as independent risk factors of tacrolimus intolerance. Conclusions These results suggested SFTC is a potential risk factor for dyslipidemia and IR after LT. Besides, rs4646450, rs6977165 and rs776746 of CYP3A5 might be the underlying genetic risks of tacrolimus intolerance. This might be useful for transplant surgeons to make clinical decisions earlier about immunosuppression use.